KOEFISIEN PERPINDAHAN MASSA DALAM EKSTRAKTOR TANGKI BERPENGADUK - Muthia Elma (INFO-TEKNIK, 2005)
liquid-liquid extraction in a mixer tank was widely used to reach a certain mass transfer rate. Mass transfer rate in a mixer tank extractor is declared as mass transfer coefficient. This research intends to learn how mass transfer coefficient does in a mixer tank extractor and variables that influence mass transfer coefficient.  Determination of mass transfer coefficient in a mixer tank extractor is a function of mixer rate and characteristic of physical system.  This system study about water – acetic acid – methyl acetic between CMC as a phase concentration in a solvent.  The influences of  variable to mass transfer coefficient in a equation of non-dimention group is; Sh=7396.05 Re0.82 Sch -0.35.For whirlmixer, rate is between 1 to 4 circle/s and solvent viscosity is between 1 to 6.18 cP, and for whirlReynold, rate is between 2500 to 1000 and whirlSchmidt is between 689.655 to 4262.07.